#### Answer

$\frac{5}{4}$

#### Work Step by Step

$\frac{43}{24}-\frac{13}{24}=\frac{43-13}{24}=\frac{30}{24}=\frac{30\div6}{24\div6}=\frac{5}{4}$

Published by
Pearson

ISBN 10:
0321825535

ISBN 13:
978-0-32182-553-7

$\frac{5}{4}$

$\frac{43}{24}-\frac{13}{24}=\frac{43-13}{24}=\frac{30}{24}=\frac{30\div6}{24\div6}=\frac{5}{4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.